DRJAMM Is Involved in the Oxidative Resistance in Deinococcus radiodurans - Cai, Jianling; Pan, Chaoming; Zhao, Ye; Xu, Hong; Tian, Bing; Wang, Liangyan; Hua, Yuejin (Frontiers in Microbiology, 2022)
Proteins containing JAB1/MPN/MOV34 metalloenzyme (JAMM/MPN+) domains that have Zn2+-dependent deubiquitinase (DUB) activity are ubiquitous across among all domains of life. Recently, a homolog in Deinococcus radiodurans, DRJAMM, was reported to possess the ability to cleave DRMoaD-MoaE. However, the detailed biochemical characteristics of DRJAMM in vitro and its biological mechanism in vivo remain unclear. Here, we show that DRJAMM has an efficient in vitro catalytic activity in the presence of Mn2+, Ca2+, Mg2+, and Ni2+ in addition to the well-reported Zn2+, and strong adaptability at a wide range of temperatures. Disruption of drJAMM led to elevated sensitivity in response to H2O2 in vivo compared to the wild-type R1. In particular, the expression level of MoaE, a product of DRJAMM cleavage, was also increased under H2O2 stress, indicating that DRJAMM is needed in the antioxidant process. Moreover, DRJAMM was also demonstrated to be necessary for dimethyl sulfoxide respiratory system in D. radiodurans. These data suggest that DRJAMM plays key roles in the process of oxidative resistance in D. radiodurans with multiple-choice of metal ions and temperatures.